2023
DOI: 10.1182/blood.2022019543
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the molecular heterogeneity of pediatric monomorphic post–solid organ transplant lymphoproliferative disorders

Abstract: Post-transplant lymphoproliferative disorders (PTLD) represent a broad spectrum of lymphoid proliferations, frequently associated with Epstein-Barr Virus (EBV) infection. The molecular profile of pediatric monomorphic PTLDs (mPTLD) has not been elucidated and it is unknown whether they display similar genetic features as their counterpart in adult and immunocompetent (IMC) pediatric patients. In this study, we investigated 31 pediatric mPTLD after solid organ transplantation, including 24 diffuse large B-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Recent molecular characterisation of paediatric BL mPTLD has shown mutational profiles of BL mPTLD consistent with sporadic BL, suggesting the need of intensive therapy, as delivered to paediatric B-NHL. 17 In keeping with that study, our series of BL patients showed a longer time from transplant to mPTLD diagnosis in MYC-rearranged cases. It is notable that five of 10 cases requiring second-line therapy in our study had either BL morphology or MYC-rearrangement, with PFS approaching significance in this subgroup, but escalation of therapy intensity in these cases was associated with outcomes comparable to the patients not needing therapy escalation.…”
Section: Effect Of Myc Status or T(8;14)supporting
confidence: 88%
“…Recent molecular characterisation of paediatric BL mPTLD has shown mutational profiles of BL mPTLD consistent with sporadic BL, suggesting the need of intensive therapy, as delivered to paediatric B-NHL. 17 In keeping with that study, our series of BL patients showed a longer time from transplant to mPTLD diagnosis in MYC-rearranged cases. It is notable that five of 10 cases requiring second-line therapy in our study had either BL morphology or MYC-rearrangement, with PFS approaching significance in this subgroup, but escalation of therapy intensity in these cases was associated with outcomes comparable to the patients not needing therapy escalation.…”
Section: Effect Of Myc Status or T(8;14)supporting
confidence: 88%